Generalized Anxiety Disorder sebagai Ide Penciptaan Seni Lukis - Rudiana, Sarah Aulia; Wiyono, Wiyono; Hamzah, Amir (Institut Seni Indonesia Yogyakarta, 2023)
Penciptaan karya seni berjudul Generalized Anxiety Disorder sebagai Ide Penciptaan Seni Lukis merupakan wujud ekspresi penulis dalam menyampaikan apa yang diderita penulis dan ketertarikan terhadap dunia psikologis dapat diimajinasikan menjadi karya seni lukis. Kesehatan mental seringkali menjadi hal yang sedikit tabu dibahas oleh masyarakat. Generalized Anxiety Disorder merupakan salah satu gangguan kesehatan mental yang ada di lingkungan sekitar kita. Seniman dapat menggunakan aspek kesehatan mental sebagai ide dalam berkarya dengan merepresentasi perasaan dan pengalaman yang didalami selama proses pembuatan. Perwujudan emosi sebagai bentuk visual dengan simbol-simbol tertentu dari penulis dengan figur antagoonis, dan protagonis. Dengan menggunakan teknik dan media akrilik, perwujudan perasaan dan pengakaman dituangkan dalam karya yang dapat dinikmati secara visual yang menonjolkan pada dua karakter utama yaitu antagonis dan protagonnis. Generalized Anxiety Disorder as an Idea for Creating Painting ArtThe creation of a work of art entitled Generalized Anxiety Disorder as an Idea for the Creation of Painting is a form of expression of the author in conveying what the author suffers and interest in the psychological world can be imagined into a work of painting. Mental health is often a little taboo for society to discuss. Generalized Anxiety Disorder is one of the mental health disorders that exist in the environment around us. Artists can use aspects of mental health as ideas in their work by representing the feelings and experiences experienced during the creation process. The embodiment of emotions as a visual form with certain symbols of the author with an antagonist figurative, and the protagonist. Using acrylic techniques and media, the embodiment of feelings and feelings is expressed in a visually enjoyable work that highlights the two main characters, the antagonist and the protagonist.